IFRS adoption, stock price synchronicity and firm-specific information in Indonesia stock market - Dwi Astuti Rosmianingrum; Nor Farizal Mohammed; Imbarine Bujang; Lianny Leo (Cogent Business & Management, 2023)
This is the first study to explore the impact of Indonesia's adoption of International Financial Reporting Standards (IFRS) on information flow and stock price informativeness throughout the pre-IFRS (2007-2011), transition (2012-2014), and post-IFRS (2015-2019) adoption periods, as determined by stock price synchronicity (SYNCH). This study examines if IFRS has reduced Indonesia's SYNCH. The empirical data show that the mean value of SYNCH was negative for each of the 13 years investigated in this study, with the post-IFRS period having the lowest value. After that, SYNCH values steadily recovered. This study used panel data regression to objectively examine the relationship between a variety of independent variables and SYNCH. This research found that requiring the adoption of IFRS will first boost the flow of private information (firm-specific information) into stock price formation and eventually reduce the surprise impact of future disclosed information. This study also contributes new knowledge by offering proof of the effects of IFRS adoption and helping standard-setters in weighing the pros and disadvantages of their choices to keep implementing IFRS in Indonesia.
Keywords: G14; M41; 650; IFRS adoption; firm-specific information; stock price synchronicity